2007
DOI: 10.5395/jkacd.2007.32.3.208
|View full text |Cite
|
Sign up to set email alerts
|

A study on fractural behavior of dentin-resin interface

Abstract: The fracture toughness test is believed as a clinically relevant method for assessing the fracture resistance of the dentinal restoratives. The objectives of this study were to measure the fracture toughness (K1C) and microtensile bond strength of dentin-resin composite interface and compare their relationship for their use in evaluation of the integrity of the dentin-resin bond.A minimum of six short-rod specimens for fracture toughness test and fifteen specimens for microtensile bond strength test was fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In a case of dentin-composite interface, many studies reported there was no significant correlation even though they had a similar pattern. 13,15,39 Dhuru and Lloyd have mentioned that the fracture stress of the repair may be a function of both the interfacial strength and defect produced by the operators'repair technique.…”
Section: Jkacd Volume 35 Number 6 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…In a case of dentin-composite interface, many studies reported there was no significant correlation even though they had a similar pattern. 13,15,39 Dhuru and Lloyd have mentioned that the fracture stress of the repair may be a function of both the interfacial strength and defect produced by the operators'repair technique.…”
Section: Jkacd Volume 35 Number 6 2010mentioning
confidence: 99%
“…Therefore, the bond strength test alone is not sufficient to decide whether a treatment has enhanced the resistance to fracture or not. 12,13 A reliable and valid method for the evaluation of bonded interfaces is needed to help predict, understand and assess clinical bonding failures.…”
Section: Introductionmentioning
confidence: 99%